Handbook of leaving religion - Enstedt, Daniel (Brill Handbooks on Contemporary Religion, 2019)
The Handbook of Leaving Religion introduces a neglected field of research with the aim to outline previous and contemporary research, and suggest how the topic of leaving religion should be studied in the future. The handbook consists of three sections: 1) Major debates about leaving religion; 2) Case studies and empirical insights; and 3) Theoretical and methodological approaches. Section one provides the reader with an introduction to key terms, historical developments, major controversies and significant cases. Section two includes case studies that illustrate various processes of leaving religion from different perspectives, and each chapter provides new empirical insights. Section three discusses, presents and encourages new approaches to the study of leaving religion.